2011
DOI: 10.1007/978-1-4419-8414-2_7
|View full text |Cite
|
Sign up to set email alerts
|

Cruzain

Abstract: Cruzain is the major papain-like cysteine protease of Trypanosoma cruzi, the etiological agent causing Chagas' disease in humans in South America. Cruzain is indispensable for the survival and propagation of this protozoan parasite and therefore, it has attracted considerable interest as a potential drug target. This chapter charts the path from the initial identification of this proteases activity and its validation as a bone fide drug target to the arduous task of the discovery of an inhibitor targeting this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 90 publications
0
55
0
2
Order By: Relevance
“…All compounds were analyzed by quantitative liquid chromatography-mass spectrometry (LC-MS) by using a SCIEX 2000 apparatus (Toronto, Canada) with positive ion electron spray ionization. LC separation was achieved by using a Luna C 18 3-m (50-by 2-mm) LC column (Phenomenex) with a mobile-phase gradient consisting of acetonitrile and 0.1% formic acid. Analysis of Cz007 was done using a 3-min gradient of acetonitrile from 35 to 95%, with MS ionization at ϩ30 eV.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…All compounds were analyzed by quantitative liquid chromatography-mass spectrometry (LC-MS) by using a SCIEX 2000 apparatus (Toronto, Canada) with positive ion electron spray ionization. LC separation was achieved by using a Luna C 18 3-m (50-by 2-mm) LC column (Phenomenex) with a mobile-phase gradient consisting of acetonitrile and 0.1% formic acid. Analysis of Cz007 was done using a 3-min gradient of acetonitrile from 35 to 95%, with MS ionization at ϩ30 eV.…”
Section: Figmentioning
confidence: 99%
“…The cysteine protease cruzipain, a member of the papain family, is essential for the viability and virulence of T. cruzi, and thus inhibitors of cruzipain are considered promising agents for Chagas disease therapies (14,15,16,17,18,19). Studies with irreversible cruzipain inhibitors have shown the biochemical impact of inhibiting cruzipain on T. cruzi.…”
mentioning
confidence: 99%
“…Once within a cell, the parasite transforms into the non-flagellar replicative amastigote form. Infection of visceral organs causes a number of mega syndromes, notably in the heart, colon, and esophagus, but heart failure is more common in infected patients (Clayton, 2010;Sajid et al, 2011). Before to host cell rupture, the amastigote form transform back into trypomastigote that can either reinvade a new host cell or be taken up via a blood meal by the insect vector (Cazzulo, Stoka & Turk, 2001;Bhattacharya, Hall, Li & Vaidehi, 2008;Clayton, 2010;Sajid et al, 2011;Calderano et al, 2014;Sayé, Miranda, di Girolamo, Camara & Pereira, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…In humans, the blood stream trypomastigote form can invade a large number of cell types (Clayton, 2010;Sajid et al, 2011). Once within a cell, the parasite transforms into the non-flagellar replicative amastigote form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation